Variability and relationship of six Indonesian shallots (Allium cepa var. ascalonicum) cultivars based on amino acid profiles and fried shallot’s sensory characteristics - Olivia Yofananda; Sobir Sobir; C. Hanny Wijaya; Hanifah Nuryani Lioe (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Yofananda O, Sobir, Wijaya CH, Lioe HN. 2021. Variability and relationship of six Indonesian shallots (Allium cepa var. ascalonicum) cultivars based on amino acid profiles and fried shallot’s sensory characteristics. Biodiversitas 22: 3327-3332. Shallot is an essential spice in the daily menu and processed food due to its unique flavor. Therefore information regarding the correlated compounds responsible for flavor in several cultivars of shallot will be important to elucidate. Since the amino acids profile is a key component of flavor character, this study aimed to determine the variability of amino acid profiles among six shallot cultivars related to fried shallot’s sensory characteristics. The six shallot cultivars were Bima Brebes, Bauji, Batu Ijo, Tajuk, Super Philip, and Rubaru. The shallot bulb was cultivated in the same area. The bulb size was analyzed using an analytical balance, the amino acids profile was analyzed using HPLC instrument, and sensory characteristics of fried shallots were analyzed using the rate-all-that-apply descriptive method. The result showed that the shallots contained a high content of glutamic acid, arginine, and aspartic acid. Based on fresh weight, Batu Ijo was significantly different than the other cultivars which comprised Tajuk, Rubaru, Bauji, Super Philip and Bima Brebes. Clustering based on amino acid profiles of the fresh bulb, they were divided into three groups. The first group consisted only Bauji, and the second group consisted of Rubaru, Batu Ijo, Super Philip and Tajuk, the third group was only Bima Brebes. Based on the sensory characteristics of fried shallots, they were divided into three groups. The first group comprised of Bauji and Tajuk, the second group comprised of Rubaru alone, and the third group comprised of Batu Ijo, Super Philip, and Bima Brebes. The Pearson correlation analysis showed that L-phenylalanine, L-arginine, and glycine have a significant positive correlation with a sweet taste of fried shallot, indicated that amino acids profile is an important parameter for shallot flavor.